2010
DOI: 10.1111/j.1440-1754.2010.01899.x
|View full text |Cite
|
Sign up to set email alerts
|

Health of Australian children in out‐of‐home care: Needs and carer recognition

Abstract: Queensland children in care have high health needs similar to those evidenced by children in care in other areas of Australia. Foster carers appear to underestimate the health needs of children in their care, demonstrating the necessity of multidisciplinary health screens and foster carer training in order to detect child health problems in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
52
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 7 publications
2
52
0
1
Order By: Relevance
“…eczema, abdominal pain, constipation and soiling) . The overall high prevalence of physical health problems is in line with other Australian studies of children in OOHC . Some of the somatic symptoms identified in the clinic may have had an underlying mental health aetiology, in line with previous studies that have shown increased somatic symptoms in children with exposure to trauma …”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…eczema, abdominal pain, constipation and soiling) . The overall high prevalence of physical health problems is in line with other Australian studies of children in OOHC . Some of the somatic symptoms identified in the clinic may have had an underlying mental health aetiology, in line with previous studies that have shown increased somatic symptoms in children with exposure to trauma …”
Section: Discussionsupporting
confidence: 88%
“…It is unsurprising that mental health and developmental concerns generated the most recommendations for further assessment or treatment. The high rates of referral for mental health care, speech therapy and ongoing paediatric care are also similar to interstate Australian studies and add to the evidence that children in OOHC warrant both careful and timely identification of health needs and access to services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high rate of health needs is likely to be attributable to many factors, including: The neglect and/or abuse that was the primary reason for involvement of Child Protective Services and placement in OOHC Trauma related to removal from family. A lack of utilisation of regular health services, including lack of response to and/or follow‐up of health needs prior to and while in OOHC The nature of OOHC: Where multiple short placements often result in further attachment issues and trauma. Health and development issues being unnoticed by short‐term carers. The child being lost to follow‐up by individual services because of the placement instability …”
Section: Discussionmentioning
confidence: 99%
“…Children in OOHC have typically experienced abuse, neglect and disrupted attachment . In a cohort of 980 Victorian Aboriginal and Torres Strait Islander children in OOHC, 87% were impacted by family violence, and 87% had a parent with alcohol or substance abuse issues .…”
mentioning
confidence: 99%